(untitled) (KYAMC Journal, 2024)
Background: Helicobacter Pylori Infection (HPI) is usually acquired during childhood, without specific treatment this infection rarely resolves spontaneously. Therefore, correct diagnosis is necessary for the effective eradication and there is no single test can be regarded as the gold standard for the identification of H. pylori. Objective: To compare the sensitivity, specificity, and accuracy of the stool antigen test, serologic test, rapid urease test, and histology for the diagnosis of H. pylori infection. Materials and Methods: This cross-sectional descriptive study was conducted at the Department of Pediatric Gastroenterology & Nutrition, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka from April 2019 to October 2021 on 54 children aged less than 18 years suspected to be H. pylori infection, who attended the outpatient as well as admitted. In a typical data sheet, a complete clinical history, exam results, and investigation reports were documented. Results were expressed as sensitivity, specificity, positive predictive value, negative predictive value and diagnostic accuracy. Results: The gastro-duodenal biopsy and Rapid Urease Test (RUT) (100%) have the highest sensitivity, followed by serology (95%), and Saturation (SAT) (70%). Highest specificity was found in gastro-duodenal biopsy 88.2% followed by RUT 67.6% & SAT 41.2% and only 32.4% by serology. The gastro-duodenal biopsy had the highest diagnosis accuracy (92.6%), followed by RUT (79.6%), serology (55.6%) and SAT (51.9%). Conclusion: In the study, the gastro-duodenal biopsy and rapid urease test both showed high sensitivity, specificity, and negative predictive value; as a result, the combination of these tests constituted the best alternative for making the diagnosis. Because of their high sensitivity, serological tests may be useful non-invasive screening methods. KYAMC Journal Volume: 14, No: 03, October 2023: 130-137.